2003
DOI: 10.7186/bgsm47200310
|View full text |Cite
|
Sign up to set email alerts
|

Sequence stratigraphic framework of Northwest Borneo

Abstract: The character of the Cenozoic sedimentary sequence of NW Borneo exhibits the interplay of eustatic sea level change and the commonly dramatic effects of tectonic events. In this paper, we show how the adoption of a unified stratigraphic nomenclature, tied to the Global Sequences of Haq et al. (1988), can help unravel the superimposition of eustatic and tectonic processes. We also assess the importance of these processes in terms of the genesis, character and the distribution of the basin fills. The results giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The new model still did not balance well with observed large scale geology, for example had clearly identified the dominant first widespread transgression to marine conditions in Sarawak was during Cycle III accelerating into Cycle IV, and yet the Morrison and Wong (2003) scheme showed relative stasis over Cycle II to mid Cycle IV. A sceptic could infer interpretation-bias as his Figures 7, 8 and 9 (summaries for Balingian, Luconia and West Baram) have a "snap to fit" appearance, where every unconformity is correlated to a eustatic sequence boundary.…”
Section: Modern Analysesmentioning
confidence: 78%
“…The new model still did not balance well with observed large scale geology, for example had clearly identified the dominant first widespread transgression to marine conditions in Sarawak was during Cycle III accelerating into Cycle IV, and yet the Morrison and Wong (2003) scheme showed relative stasis over Cycle II to mid Cycle IV. A sceptic could infer interpretation-bias as his Figures 7, 8 and 9 (summaries for Balingian, Luconia and West Baram) have a "snap to fit" appearance, where every unconformity is correlated to a eustatic sequence boundary.…”
Section: Modern Analysesmentioning
confidence: 78%
“…(D) Alternative geological map of study area (after Liechti et al, 1960) that also recognizes the Tukau Formation and, in Nagarajan et al (2015), the Miri Formation (asterisk) in the area of the studied Lambir Formation. Mapped positions for the WBL are from (1) Kessler 2010 to Cycles IV to lower V (Ho, 1978;Morrison & Lee, 2003;Wannier et al, 2011;Jong et al, 2017) and TB 2.4 to 2.5 (Torres et al, 2011;Balaguru & Lukie, 2012), underlain by the Middle Miocene Unconformity (MMU) dated at ca 15.5 Ma with a ca 0.5 Myr gap (Wannier et al, 2011) and approximately overlain by the Lower Intermediate Unconformity (LIU) dated at ca 12.1 Ma (Torres et al, 2011;Balaguru & Lukie, 2012) (see also Levell, 1987). (F) Interpreted time-averaged gross depositional maps for the western BDP at approximately 15.0 Ma, 14.1 to 12.7 Ma, 12.7 to 12.1 Ma and 12.1 to 9.6 Ma (modified after Mazlan, 1999;Hutchison, 2005;Cullen, 2010;Jong et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This outcrop study is an analogue to the West Baram Delta, where the two lithofacies identified are shown in the cross section of depositional phase of Baram Delta as shown by a model in Figure 8. Baram Delta began progradation in the Middle Miocene and encounter rapid deltaic deposition throughout Late Miocene (Morrison and Wong 2003). The fall of eustatic sea level at this time has resulted in lowstand sand deposition in deepwater region which also might contribute to the formation of silty shale with high organic matter as what can be seen in grey shale around here.…”
Section: Lithofacies Identificationmentioning
confidence: 72%